Teksty naukowe i techniczne doby średniopolskiej jako źródło badań historycznojęzykowych - Szczaus, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
In the Middle-Polish period numerous texts on science and technology were written. Linguists used to pay little attention to those writings – researchers analysed the terminology and noted the morphological manifestations of the scholarly style as well as the manifestations of consistency of historical scientific texts. The issues such as the emergence of the principles of drafting ancillary texts (footnotes, references, bibliography lists); the early development of the scientific press publications (popular-scientific press) in the Polish language and the emergence of new genres of text assisting the scientific aspects of life were of little interest to linguists. Moreover, a large body of historical scientific and technical texts remained entirely unknown to a vast number of readers as the overwhelming majority of those publications have never been republished. In recent years, thanks to–among others–quickly progressing digitisation, it is increasingly easier to access the old scientific and technical texts. Consequently, more and more attention is paid to them by researchers who emphasize that the development of the Polish language was influenced not only by the transformations of the artistic language but also by other stylistic varieties of Polish, including the scholarly style.